Yields and yield gaps in lowland rice systems and options to improve smallholder production - Awio, T.; Senthilkumar, Kalimuthu; Dimkpa, C.O.; Otim-Nape, G.W.; Struik, P.C.; Stomph, T.J. (MDPI, 2022)
Increasing productivity per unit area, hence closing the yield gap, is key to meeting cereal demand in sub-Saharan Africa. We assessed, with 114 farmers, the contribution of recommended agronomic practices (RAP) with or without NPK fertilization on yield gaps, and options to intensify productivity. Treatments included farmers’ practice (FP) as control, RAP with and without NPK, and farmer-selected best practices geared towards intensification (farmers’ intensification practice, FIP). RAP without fertilization and FIP significantly increased grain yield, each by ca. 12%, whereas RAP+NPK application produced ca. 33% extra yield, over FP. RAP gave the highest mean net income (ca. USD 220 ha−1), fertilizer costs made RAP+NPK gave the lowest mean net income (ca. USD 50 ha−1). Weeding and fertilization timing contributed most to yield variation among fields. Delay in weeding and fertilization created an average yield loss of 5.3 and 1.9 g m−2, per day delay, respectively. Exploitable yield gap averaged 24 and 29%, respectively, across treatments and under FP. RAP, FIP, and RAP+NPK reduced the exploitable yield gap to 25, 26, and 12%, respectively. We conclude that different yield gap levels can be exploited by smallholder farmers in lowland rice systems as RAP, FIP, and RAP+NPK allow yield gap reduction, although fertilization poses a risk to profit at current rice and fertilizer prices. To realize yield gains, farmers with good water management should combine timely weeding with other crop management practices.